1980
DOI: 10.1177/070674378002500707
|View full text |Cite
|
Sign up to set email alerts
|

Untoward Effects following Combined Neuroleptic-Lithium Therapy: Cardiac Arrhythmias and Seizure

Abstract: This case study deals with a cardiac and respiratory arrest suffered by a manic patient on maintenance lithium therapy who was treated with chlorpromazine and haloperidol. A brief discussion is presented of the possible relationship of these arrests with the drug therapy and some suggestions are presented to avoid these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In another study (35), two of 30 patients receiving lithium and a neuroleptic developed severe tremor. Cases in which use of lithium combined with a neuroleptic resulted in severe neurotoxicity, such as delirium, seizures, tardive dyskinesia, encephalopathy, or EEG abnormalities, have been reported, as have hypotension and cardiac arrhythmias (44)(45)(46)(47)(48)(49)(50)(51)(52). However, Krishna et al (34) reported that neurologic symptoms are usually mild and resolve with discontinuation of medication.…”
Section: Combinations With Lithiummentioning
confidence: 98%
“…In another study (35), two of 30 patients receiving lithium and a neuroleptic developed severe tremor. Cases in which use of lithium combined with a neuroleptic resulted in severe neurotoxicity, such as delirium, seizures, tardive dyskinesia, encephalopathy, or EEG abnormalities, have been reported, as have hypotension and cardiac arrhythmias (44)(45)(46)(47)(48)(49)(50)(51)(52). However, Krishna et al (34) reported that neurologic symptoms are usually mild and resolve with discontinuation of medication.…”
Section: Combinations With Lithiummentioning
confidence: 98%
“…Haloperidol is a commonly used antipsychotic drug that has potential to block I Kr channels in a concentrationdependent manner in vitro [13]. While there are a number of case reports in the literature that describe haloperidolinduced QT prolongation [14,15] and torsades de pointes arrhythmias [16], the ability of haloperidol to prolong the QT interval at low doses routinely used in clinical practice has not been systematically evaluated. We compared the heart rate-corrected QT interval using the subject-specific correction to results obtained by Bazett's and Fridericia's corrections.…”
Section: Introductionmentioning
confidence: 99%